Estimating a semi-parametric duration model without specifying heterogeneity - Jerry A. Hausman; Tiemen M. Woutersen (Centre for Microdata Methods and Practice (cemmap), 2005)
This paper presents a new estimator for the mixed proportional hazard model that allows for a nonparametric baseline hazard and time-varying regressors. In particular, this paper allows for discrete measurement of the durations as happens often in practice.
Keywords: 330; Mixed Proportional Hazard Model; Time-varying regressors; Heterogeneity; Mikroökonometrie; Theorie; Mikroökonometrie; Theorie